Kata Ganda Bahasa Melayu: Tinjauan Bentuk Berdasarkan Data Korpus by Zaidi Ismail, Kuala Lumpur: Dewan Bahasa dan Pustaka, 2008. pp. xx + 90. (KEMANUSIAAN The Asian Journal of Humanities, 2012)
There are a number of studies that identify Malay reduplication as part of Malay lexical derivation. Earlier publications, within which Malay duplication is analysed, include those of Asmah (1975; 1987), Tham (1977), Liaw (1985; 1999), Zaharani (1991) and Awang Mohamad Amin (1992) with the publication under review suggesting a renewed interest in the study of Malay reduplication in the 21st century. This is then a continuation of the trend of other such recent studies as Mohd Gani Ahmad (2003), Zaharani (2007) and Sew (2007; 2011), all of which position Malay reduplication as part of a significant Malay lexical derivation.